2003
DOI: 10.1242/jeb.00113
|View full text |Cite
|
Sign up to set email alerts
|

The blood volumes of the primary and secondary circulatory system in the Atlantic codGadus morhuaL., using plasma bound Evans Blue and compartmental analysis

Abstract: SUMMARYThe volume of the primary (PCS) and secondary (SCS) circulatory system in the Atlantic cod Gadus morhua was determined using a modified dye dilution technique. Cod (N=10) were chronically cannulated in the second afferent branchial artery with PE-50 tubing. Evans Blue dye was bound to harvested fish plasma at a concentration of 1 mg dye ml-1plasma, and injected at a concentration of 1 mg kg-1 body mass. Serial sampling from the cannula produced a dye dilution curve, which could be described by a double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…It has been reported that the secondary vascular system can range from 10-50% to nearly twice the volume of the primary circulation (Steffensen and Lomholt, 1992; Bushnell et al, 1998;Gallaugher and Farrell, 1998;Skov and Steffensen, 2003). The magnitude of other effects, such as splenic release of RBCs, increases in RBC volume and blood volume reduction (see above) may also play a role in differences in the magnitude of the haematocrit change with increased RBCs flow into the SVS of different fish species.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that the secondary vascular system can range from 10-50% to nearly twice the volume of the primary circulation (Steffensen and Lomholt, 1992; Bushnell et al, 1998;Gallaugher and Farrell, 1998;Skov and Steffensen, 2003). The magnitude of other effects, such as splenic release of RBCs, increases in RBC volume and blood volume reduction (see above) may also play a role in differences in the magnitude of the haematocrit change with increased RBCs flow into the SVS of different fish species.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 98%
“…The volume of the SVS can range from 10-50% to nearly twice the volume of the primary circulation (Bushnell et al, 1998;Gallaugher and Farrell, 1998;Skov and Steffensen, 2003;Steffensen and Lomholt, 1992) and therefore may serve to buffer osmotic and ionic changes in the primary circulation. Under resting conditions, no red blood cells (RBCs) are present in the SVS.…”
Section: Introductionmentioning
confidence: 99%
“…Perfusion rate to the secondary circulation is likely under a neurotransmitter or humoral control (Vogel 1985a;Skov and Bennett 2004b). Since the secondary circulation forms a capillary network on the body surface (Vogel 1985a), the fluid could be diluted with environmental water and the gradient of protein concentration may be maintained by the low flow rate in the secondary circulation (Skov and Steffensen 2003). However, this hypothesis conflicts with the finding in the present study that the levels of the lower-molecular-weight substances appear to be similar between two circulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a contribution, if any, of the secondary circulation in the osmoregulation may dependent on its volume, flow rate and turn over rate, which are subjects of active debates. For instance, the volume of the secondary circulation was considered to be high (150% of primary circulation; Steffensen and Lomholt 1992), but recent studies suggest that it is much smaller (10-50%; Bushnell et al 1998;Skov and Steffensen 2003). The large difference is attributed to the assumption of whether albumin, a commonly used protein marker for measuring blood volume, is permeable to fish capillaries or not.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitemia estimates were obtained by counting trypanosomes in aliquots of isolated buffy coat/leukocyte fractions. Intensity estimates were calculated using cod red blood volumes (primary circulatory system) extrapolated with the allometric relationship found by Skov and Steffensen (2003).…”
Section: Methodsmentioning
confidence: 99%